The Value of Public Information in Monopoly - Ottaviani, Marco; Prat, Andrea (Econometrica, 2001)
The logic of the linkage principle of Milgrom and Weber (1982) extends to price discrimination. A non-linear pricing monopolist who sells to a single buyer always prefers to commit to publicly reveal information affiliated to the valuation of the buyer. This is also valid when the value of the buyer affects the opportunity cost of the seller.